Rodríguez Cidre, E. (2010). Cautivas Troyanas. El mundo femenino fragmentado en las tragedias de Eurípides. Córdoba, Ediciones El Copista - Romero-Mariscal, Lucia (Revista Archai, 2016)
Reseña: Rodríguez Cidre, E. (2010). Cautivas Troyanas. El mundo femenino fragmentado en las tragedias de Eurípides. Córdoba, Ediciones El Copista